Marketing : - Kerin, Roger A. (John Wiley & Sons, Inc., 2013)
Marketing: The Core 5e by Kerin, Hartley and Rudelius continues a tradition of leading the market with contemporary, cutting-edge content presented in a conversational student-oriented style, supported by the most comprehensive, innovative, and useful supplement package available. This text and package is designed to meet the needs of a wide spectrum of faculty – from the professor who just wants a good textbook and a few key supplements, to the professor who wants a top-notch fully integrated multimedia program. Marketing: The Core utilises a unique, innovative, and effective pedagogical approach developed by the authors through the integration of their combined classroom, college, and university experiences.